Strategi Manajemen Badan Usaha Milik Desa Dalam Meningkatkan Pendapatan Asli Desa di Desa Sukajadi Kecamatan Sadananya Kabupaten Ciamis - Adella Almy Ataris; Kiki Endah; R. Rindu Garvera (Papsel Journal of Humanities and Policy, 2024)
This research is motivated by the non-optimal management of Village-Owned Enterprises in an effort to increase Village Original Income in Sukajadi Village, Sadananya District, Ciamis Regency. The method used in this research is qualitative research method. Data collection techniques in this study include literature study, field study (observation and interviews) and documentation. The informants in this study were 6 people. The data analysis technique in this study by means of data reduction, data presentation, conclusions and verification. This study aims to determine the Management of Village-Owned Enterprises on increasing Village Original Income in Sukajadi Village, Sadananya District, Ciamis Regency. The author uses qualitative data analysis techniques through data processing of interview results and observation results to draw conclusions so as to answer the problems in the study. The results showed that the Management of Village-Owned Enterprises in Efforts to Increase Village Original Income in Sukajadi Village, Sadananya Subdistrict, Ciamis Regency is already running, but it is not optimal because problems are still found, including: unprepared cooperation with the private sector, limited number and quality of labor, limited budget for new business development, management training programs that are rare and less than optimal, readiness and skills of BUMDes members in management and administration are still lacking, financial reporting that is not ready to be carried out.Keywords: Management, BUMDes, Village Original Revenue